Carotid intraplaque hemorrhage on vessel wall MRI does not correlate with TCD emboli monitoring in patients with recently symptomatic carotid atherosclerosis. Issue 5 (October 2017) - de Havenon, Adam; Tirschwell, David; Majersik, Jennifer J; McNally, Scott; Stoddard, Gregory; Moore, Anne; Mossa-Basha, Mahmud
Background: Carotid intraplaque hemorrhage (IPH) seen on vessel wall MRI is associated with an increased risk of stroke or transient ischemic attack, as are microembolic signals (MES) detected by transcranial Doppler (TCD). We sought to examine the association between IPH and MES in acute stroke patients with symptomatic carotid atherosclerosis. Methods: Through a retrospective chart review, we included patients from 2011 to 2013 with acute ischemic stroke due to carotid atherosclerosis of varying stenosis who had both 3D volumetric MRI of the neck and TCD emboli monitoring. Results: Twenty-four patients met the inclusion criteria. Mean time from stroke to MRI was 1.4 ± 1.9 days and to TCD was 2.6 ± 2.4 days. MES was seen in 10 patients (42%) and IPH was present in seven patients (29%), but we did not find a relationship between MES and IPH ( p = 0.64). Conclusion: In patients with recent acute ischemic stroke attributed to carotid atherosclerosis, we did not detect an association between the presence of IPH and MES. While this small study may be underpowered, an alternate explanation is that MES and IPH reflect vulnerable carotid atherosclerosis through different mechanisms. This untested concept warrants prospective study in a larger cohort.